Assessment of psycho-emotional symptoms in cancer patients in an Oncology-Palliative Care Department from Romania - Roxana Andreea Rahnea-Nita; Laura Florentina Rebegea; Elena Gabriela Valcu; Mihaela Dumitru; Radu Valeriu Toma; Mihai Georgescu; Georgia Luiza Serbanescu; Maria Alexandra Barbu; Georgiana Bianca Constantin; Gabriela Rahnea-Nita (Journal of Mind and Medical Sciences)
Introduction. Anxiety and depression have an increased prevalence in cancer patients, especially in those in an advanced stage of the disease. These disorders have a major impact on the social life, existential concerns and quality of life of cancer patients. Materials and Methods. A number of 114 consecutive patients were included in the study (in a period of 2 weeks) who were screened for anxiety, depression and for other common symptoms, using Hospital Anxiety and Depression Scale (HADS) and Edmonton Symptom Assessment System (ESAS). Results. Regarding the age - the abnormal level of anxiety and depression: the percentage of patients over 65 years was higher than the percentage of patients under 64 years, both in terms of anxiety and depression. Regarding the Performance status ECOG - abnormal level of anxiety and depression: the percentage of patients with ECOG = 3-4 is higher than that of patients with ECOG = 0-2. Results. The increased prevalence of anxiety and depression requires psychological counseling and treatment. It is important for these symptoms to be identified as soon as possible, in order to provide a good quality of life. Conclusions. The model we propose is for the HADS to be a screening tool on admission to a palliative care ward, for certain categories of patients.